Designing a Financial Model for Oil, Gas, and Petrochemical Industry Projects Based on Corporate Governance Approach - Rahimian, Morvarid; Azizi, Mojtaba (Management Strategies and Engineering Sciences, 2025)
Financing oil, gas, and petrochemical industry projects, as a critical pillar of economic growth and development, requires a transparent and effective mechanism. The objective of the present study is to design a financial model for oil, gas, and petrochemical industry projects based on a corporate governance approach. This research is exploratory in nature and adopts a qualitative methodology. The study was conducted through interviews with 15 experts in the field. A snowball sampling method was employed for data collection, and the extracted data from documents and interviews were categorized and analyzed using thematic analysis. Ultimately, 60 initial codes, 17 basic themes, and 7 organizing themes were identified. The organizing themes include: the role of banks in supporting energy projects, banking and credit policies and regulations for the energy sector, bank facilities available for oil, gas, and petrochemical projects, risk management in energy projects, credit evaluation indicators for energy-oriented companies, financing challenges in the oil and gas industry, and stability and sustainability of energy-based companies. Finally, the interpretive structural modeling (ISM) method was used to derive the final model. The proposed model can ultimately serve as a strategic framework for policymakers, financial institutions, and energy industry managers to improve the financing process through a transparent, accountable, and sustainable approach.